Diversifikasi Rasa, Manajemen Produksi dan Transformasi Pemasaran: Strategi Kebertahanan Bisnis Farida Bakery - Wulandari, Riza; Lilis Yuningsih; Tria Hikmah Fratiwi; I Gusti Ngurah Agung Ananda Putra; Ni Luh Putu Wulandari (Insan Kreasi Media, 2023)
The sustainability of processed food in Indonesia is inseparable from the role of economic actors, one of which is the home industry. Mrs. Farida Azis is part of the business activists from the home industry business group in Denpasar. The purpose of the community service is to find out 3 aspects partner's problems, namely aspects of flavor diversification, production management, and marketing transformation. The method used in this activity are observations, existing partners, survey of production and support equipment, Distribution of production equipment and flavors, packaging and logo design, distribution/provision of new packaging and logos, marketing transformation. The results of this community service activity have produced solutions from the production management aspect in the form of additional equipment, namely a 3-tray aluminum type oven machine, and an idea life multi-speed Premium Quality Idea life mixer (IL221s). While in the aspect of flavor diversification there are additional variants of cheese, almond, Choco ball flavors. Partners are also supported in terms of marketing aspects which have been given a logo and packaging that includes the partner's identity and marketing transformation, namely from the creation of Instagram social media under the name Farida bake. Overall, all aspects that are an obstacle for partners have received solutions that suit the needs of partners. The activity went well and smoothly and there was hope from the partners that this activity would not only stop until the community service program was completed, but could continue to foster other MSMEs that needed assistance.